Associations Between Delivery Mode and Early Childhood Body Mass Index Z-Score Trajectories: A Retrospective Analysis of 2,685 Children From Mothers Aged 18 to 35 Years at Delivery - Zhang, Lihong; Huang, Liuxia; Zhao, Zhiyuan; Ding, Renjuan; Liu, Hongnian; Qu, Wenchao; Jia, Xiao (Frontiers in Pediatrics, 2020)
Objective: To investigate the association between cesarean delivery (CD) and trajectory patterns of age- and sex-specific body mass index (BMI) z-score in early childhood. Methods: A retrospective cohort study was conducted among 2,685 children whose maternal age at the time of birth were between 18 and 35 years, and birth data and anthropometric measurement data during their ages 3 to 60 months were collected. A group-based trajectory modeling approach was used to identify distinct BMI z-score trajectories, and multinomial logistic regressions were applied to estimate the associations between CD (both elective and non-elective combined), elective and non-elective CD and BMI z-score trajectory classes. Results: Of the 2,685 participants, 46.5% (N=1,248) were born by vaginal delivery (VD), 20.7% (N=556) by elective CD, and 32.8% (N=881) by non-elective CD, respectively. Five BMI z-score trajectory patterns were identified, and they were “increasing from moderate to high” (10.1%, n = 270), “increasing from mild to moderate” (34.2%, n = 919), “increasing from low to high” (10.5%, n = 283), “stable mild” (30.1%, n = 808), and “stable low” (15.1%, n = 405) groups. Compared with children delivered by VD, those who delivered by CD (both elective and non-elective combined), elective CD, and non-elective CD were associated with the “increasing from moderate to high” trajectory (odds ratio [OR]=1.61, 95% confidence interval [CI]: 1.13-2.29, OR=1.64, 95%CI:1.06-2.54, OR=1.59, 95%CI:1.05-2.39, respectively), and were also associated with the “increasing from low to high” trajectory (OR=1.60, 95%CI:1.17-2.19, OR=1.75, 95%CI:1.16-2.63; OR = 1.53, 95%CI: 1.00-2.34, respectively). Conclusion: Both elective and non-elective CD were associated with risk of accelerated weight gain in early childhood.